Historiografia pedagogiczna w czasopismach tradycyjnych i elektronicznych - Sławomir, Sztorbyn (Biuletyn Historii Wychowania, 2009)
Scientific and research periodicals play an extremely important part in popularizing (and promoting) results of research studies, though this role is not equally appreciated across different domains of science. This becomes apparent if we compare the number of traditional and electronic titles of periodicals in such disciplines as medicine, natural science and exact science on the one side, and those that represent the humanities, broadly understood, on the other. The advantage of electronic content in the former group is overwhelming. Nowadays, we use two terms in relation to periodicals available online and launched on the electronic platform. The terms make a distinction between a degree of their involvement in the cyber space. “Digitalization” means a certain transitory state between traditional periodicals in print and virtual publications; in other words, a product of “digitization” is an electronic copy (e.g. a scanned text) of a text originally published in print, whereas the notion of “digital authorship (the author as digital producer), in Polish: cyfryzacja” deals with an entirely electronic publication with specific properties underlined by multimedia and hypertext capabilities. Digital research information as an entirely new quality has not been yet appropriately appreciated. The history of education as a discipline of research does not have its own electronic platform that would offer peer-reviewed research papers in Open Access (OA), e-books or electronic document repositories. For the time being, the most recent Polish periodical within this discipline, i.e. Biuletyn Historii Wychowania, has only a front page, ToCs and a masthead available online, without access to full-text electronic content.